Is monitoring of antiplatelet therapy by light transmission aggregometry dependent on instrument and reagent used?. (15th June 2021) - Monteyne, Tinne; Heireman, Laura; Hemelsoet, Dimitri; van Schaik, Ron H.N.; Devreese, Katrien M.J.
Abstract: Introduction: Light transmission aggregometry (LTA), used to detect clopidogrel resistance in patients under antiplatelet therapy, is prone to multiple variables potentially influencing results and interpretation. Currently, no attention is given to type of aggregometer or reagent used. The aim of this study was to evaluate the interassay variability between two aggregometers (Chronolog700 and TA‐8V), using two different ADP reagents (Chrono‐Par ® and Agro‐Bio ADP) in patients under clopidogrel therapy. Additionally, LTA results were correlated to CYP2C19 ‐polymorphism. Methods: Light transmission aggregometry was performed in 20 healthy individuals and 30 patients using both aggregometers, and applying two different reagents (2.5 and 5 µmol/L). The maximum platelet aggregation (ADPmax ), the platelet aggregation at 6 minutes (ADP6min ), and the percentage of disaggregation at 6 min (ADP%disaggr ) were compared between four applied combinations. Additionally, 23 clopidogrel‐resistant patients according to Chronolog700‐Chrono‐par ® ADP reagent analysis were tested for CYP2C19*2 polymorphism. Results: Comparison of the LTA of healthy individuals revealed a significant lower ADPmax, lower ADP6min, and higher ADP%disaggr with the TA‐8V aggregometer compared to Chronolog700, regardless of the reagent. In contrast, LTA results in patients are depending on the reagent, with significant higher ADPmax and ADP6min and lower ADP%disaggr using Chrono‐Par ® compared to Agro‐Bio ADP reagent. All intermediate clopidogrel metabolizers ( CYP2C19*2 carriers) were correctly classified as clopidogrel resistant using Chrono‐Par ®, in contrast to the Agro‐Bio ADP reagent. Conclusion: Light transmission aggregometry in clopidogrel‐treated patients is mainly depending on the type of ADP reagent. Comparison of LTA with genotype reveals that the choice of instrument seems less influencing. In contrast, in the healthy individuals, differences could be attributed to the instrument.